Түүхэн хэл шинжлэлийн судалгааны аргазүйд анхаарууштай зарим зарчимын тухай - Ts.Shagdarsuren (Acta Mongolica, 2007)
Энэхүү өгүүлэлийг ОХУ-ын нэрт түрэгч Эдхям Рахимович Тенишев (1921-2004) профессорын гэгээн дурсхалд зориулав. The author underlines the importance of the following principles regarding the methodology of the researches on historical linguistic illustrating his ideas on the concrete data of both Mongolian and other Altaic languages: - In the comparative studies of the scripts not only the external form likeness must be taken into account, but also the internal contest and philosophical background have to be considered as well. - A study of common-root words in relative languages belonging to the same ethnic group can not be limited by entry words in translational dictionaries, as an additional criteria a semantic field has to be taken into account. - In a comparative study of languages the shades of differences in such aspects as common-root words, forms having the same origin, but developed independently and in parallel, loan-words, accidental similarities and so on have to be clarified. - In accordance with the principle "A language is a system" every aspect of a language has to be considered in its own level distinguished from the other similar ones. - To be always aware of "the principle" that the structure of a Mongolian word never can be explained according to the Cyrillic orthography, where the typological peculiarities of the Mongolian language are reflected by no means correctly unlike the literary Mongolian language presenting the samples of the Mongolian type of thinking. This work is dedicated to the memory of professor E. R. Tenishev (1921-2004), turcologist of Russian Federation.